2019
DOI: 10.1001/jamaophthalmol.2019.2885
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Stargardt Disease as Determined by Fundus Autofluorescence Over a 12-Month Period

Abstract: IMPORTANCESensitive outcome measures for disease progression are needed for treatment trials of Stargardt disease.OBJECTIVE To estimate the progression rate of atrophic lesions in the prospective Natural History of the Progression of Atrophy Secondary to Stargardt Disease (ProgStar) study over a 12-month period. DESIGN, SETTING, AND PARTICIPANTSThis multicenter prospective cohort study was conducted in an international selection of tertiary referral centers from October 21, 2013, to February 15, 2017. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 32 publications
6
73
0
2
Order By: Relevance
“…The association between the RPE atrophy size at baseline and rate of its enlargement over the follow-up is in agreement with the results of both the retrospective and prospective cohorts of the ProgStar study. 30,31 In accordance with previous studies, 30,31 patients with multifocal disease had faster RPE-atrophy enlarging rates. Similarly, SW-FAF pattern 3, characterized by extensive changes within and beyond the vascular arcades and a heterogeneous background FAF, was a predictor of faster disease progression.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The association between the RPE atrophy size at baseline and rate of its enlargement over the follow-up is in agreement with the results of both the retrospective and prospective cohorts of the ProgStar study. 30,31 In accordance with previous studies, 30,31 patients with multifocal disease had faster RPE-atrophy enlarging rates. Similarly, SW-FAF pattern 3, characterized by extensive changes within and beyond the vascular arcades and a heterogeneous background FAF, was a predictor of faster disease progression.…”
Section: Discussionsupporting
confidence: 89%
“…This value was higher than the one reported by the retrospective analysis of Natural History of the Progression of Atrophy Secondary to Stargardt Disease (ProgStar) study, which estimated a mean progression of definitely decreased SW-FAF signal of 0.51 mm 2 /year, 30 but it was only slightly slower than the rate found in the prospective analysis of the ProgStar study (0.76 mm 2 /year). 31 Müller et al 4 have reported a mean rate of RPE-atrophy enlargement of 0.89 ± 0.13 mm 2 /year in ABCAArelated retinopathy eyes. Whereas both the ProgStar and Müller et al 4 used the mean as a measure of central tendency, it might be not appropriate in our series as the distribution of progression rates was highly rightskewed ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Autofluorescence imaging may serve as a monitoring tool, and decreased autofluorescence area measurements can be used as a structural outcome for interventional clinical trials that aim to slow disease progression. 17 Ultrawide field FAF has now allowed for the classification of the posterior pole and peripheral fundus FAF findings in STGD. [18][19][20][21] OCT is an invaluable modality in all macular diseases, which in STGD identifies and sensitively quantifies the degree and extent of outer retinal loss (photoreceptor layers) and RPE atrophy (figure 1C,D).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Although the clinical features of STGD1 are well-described, debate remains regarding the exact sequence of tissue loss in this disease (e.g., whether RPE loss precedes photoreceptor loss, or vice versa). Most imagingbased studies of progression in STGD1 have assessed the area of RPE loss, which is readily measured using en face fundus autofluorescence (FAF) imaging 9,[11][12][13][14][15] . However, recent studies using optical coherence tomography (OCT) have suggested that photoreceptor loss may actually precede RPE loss 16,17 .…”
mentioning
confidence: 99%